KEBIJAKAN PERTANAHAN PEMERINTAH KOLONIAL HINDIA-BELANDA DI BALI - Yogi Sumakto (Jurnal ADIL, 2015)
AbstractThis study examines the process (dynamics) of the development of policies on land tenure during the Dutch colonial period in Bali. The study aims to examine policies on land in the agricultural sector, particularly in relation to the social economic impacts of the colonial administration’s land tenure policies in Balinese villages. Peasants as direct producers who are at the very bottom of a larger social-economic structure find themselves bearing the heaviest impact, while farmers or the elite group of non-producer instead reaps up benefits from a wide variety of mechanisms implemented to withdraw surpluses from peasants.Keywords: peasant, policy, land tenure, Dutch colonial governmentAbstrakTulisan ini mempelajari proses (dinamika) perkembangan kebijakan pengaturan penguasaan tanah pada masa pemerintahan kolonial Hindia-Belanda di Bali. Dalam kajian ini hendak disoroti bagaimanakah kebijakan pertanahan di bidang agraris; khususnya berkenaan dengan implikasi sosial-ekonomi dari kebijakan penguasaan tanah pemerintah kolonial tersebut di pedesaan di Bali. Kaum petani sebagai produsen langsung berada pada bagian terbawah dari struktur sosial-ekonomi yang lebih besar selalu memikul beban yang berat sementara itu petani bukan-produsen atau golongan elit bukan-produsen lainnya selalu memperoleh keuntungan-keuntungan dari berbagai mekanisme penarikan surplus petani.Kata kunci: petani, kebijakan, penguasaan tanah, pemerintah kolonial hindia-belanda